(untitled) (Interfaces: A Journal of Medieval European Literatures, 2024)
Number 11 of Interfaces contains a thematic issue entitled Occasional Literature and Patronage in Later Medieval and Early Modern Periods, edited by Nikos Zagklas and Ingela Nilsson.